Karakteristik Fisik Selulosa Pelepah Nipah (Nypa fruitcan) dengan Hidrolisis Asam Kuat - Ari Kristiningsih; Khoeruddin Wittriansyah; Hety Dwi Hastuti; Jenal Sodikin (Universitas Djuanda, 2025)
Nypa palm (Nypa fruticans) possesses various potential uses, one of which is as a source of cellulose. Cellulose can be a raw material in industries such as paper production, pharmaceuticals, and biomaterials. However, the fiber of the nipa palm frond tends to be brittle and fragile. Reducing the particle size of the fiber can enhance its mechanical strength, which can be achieved through acid hydrolysis using a 10% strong acid solution. This study aims to characterize the cellulose extracted from nipa palm fronds after acid hydrolysis. The alpha-cellulose content obtained was 39.626%, with a lignin content of 18.633%. Morphological characterization revealed that the cellulose particles ranged from 615.814 μm to 840.719 μm in size. Scanning Electron Microscope–Energy Dispersive X-ray (SEM-EDX) analysis showed that the fibers were elongated with irregular lengths and were composed primarily of carbon and oxygen elements. Fourier Transform Infrared (FTIR) spectroscopy identified the presence of O–H, C–H, and C–O functional groups as the main components of cellulose, along with C=O groups associated with lignin. These findings indicate that acid hydrolysis effectively reduces the particle size of nipa palm frond fibers and enhances their physical characteristics, making them more suitable for advanced material applications.